Main Causes of Exudative Otitis Media Development in Children and Effective Treatment Methods (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Otitis media, including its exudative form, is known to be one of the most prevalent diseases among children. In infants and preschool-aged children, the disease often progresses with minimal or no clinical symptoms, which may lead to unnoticed hearing decline and, consequently, delayed diagnosis. Even a minimal degree of hearing impairment can negatively affect the development of auditory perception, speech abilities, and higher cortical functions in a child.Since pediatricians are the first specialists to regularly monitor children, they most frequently encounter the initial manifestations of exudative otitis media. Therefore, it is essential for them to have a comprehensive understanding of the mechanisms, primary causes, and risk factors contributing to the development of this disease. The initial part of this literature review highlights the main theories of exudative otitis media pathogenesis, the participation of viral and bacterial microflora, obstruction of the auditory tube due to nasopharyngeal neoplasms, craniofacial and chromosomal anomalies, allergic conditions, rhinosinusitis, and the role of adenoiditis.